Factors associated with the arrival of smartphone-activated first responders before the emergency medical services in Out-of-Hospital cardiac arrest dispatch. (April 2023) - Gamberini, Lorenzo; Del Giudice, Donatella; Saltalamacchia, Stefano; Taylor, Benjamin; Sala, Isabella; Allegri, Davide; Pastori, Antonio; Coniglio, Carlo; Gordini, Giovanni; Semeraro, Federico; ,
Graphical abstract: Graphical abstract Abstract: Background: First responder programs were developed to speed up access to cardiopulmonary resuscitation and defibrillation for out-of-hospital cardiac arrest (OHCA) victims. Little is known about the factors influencing the efficiency of the first responders arriving before the EMS and, therefore, effectively contributing to the chain of survival. Objectives: The primary objective of this retrospective observational study was to identify the factors associated with first responders' arrival before EMS in the context of a regional first responder program arranged to deliver automated external defibrillators on suspected OHCA scenes. Methods: Eight hundred ninety-six dispatches where FRs intervened were collected from 2018 to 2022. A robust Poisson regression was performed to estimate the role of the time of day, the immediate availability of a defibrillator, the type of first responder, distances between the responder, the event and the dispatched vehicle, and the nearest available defibrillator on the probability of responder arriving before EMS. Moreover, a geospatial logistic regression model was built. Results: Responders arrived before EMS in 13.4% of dispatches and delivered a shock in 0.9%. The immediate availability of a defibrillator for the responder (OR = 3.24) and special categories such as taxi drivers and police (OR = 1.74) were factors significantly associated with the responder arriving before EMS. Moreover, a geospatial effect suggested that first responder programs may have a greater impact in rural areas. Conclusions: When dispatched to OHCA scenes, responders already carrying defibrillators could more probably reach the scene before EMS. Special first responder categories are more competitive and should be further investigated.